Crisis Management of Thai Airways International Public Company Limited - Benjamapa, chitipat; Laothamatas, Anek; Srison, Jiraporn (Political Science Critique, 2022)
The objectives of this research were: 1) to investigate factors that influence the administrative mechanism of Thai Airways International Public Company Limited, 2) to discover problems and threats of crisis management of the company, and 3) to propose crisis management guideline to the company. This research applied the qualitative methodology, collecting information and data from empirical evidence, documentary research, and in-depth interviews with nine key informants. The interview questions were aimed to investigate the key informants’ attitudes and to discover the overall crisis management of the company as well as problems and barriers. The results revealed that the management team of Thai Airways International Public Company Limited thoroughly understood their roles as well as responsibilities related to crisis management, preventing the expansion of crisis through the implementation of appropriate policies and measures. The research proposed three guidelines on the company’s crisis management: 1) the company’s management structure must be concise without complicated networks; 2) its policy formulation must be consistent with that of the government; and 3) its leaders should focus on working for success, take part in human resource development, have knowledge of aviation business and risk and budget management, and contribute to a good working environment for their staffs to help the company recover from financial loss.